Investigation on the combustion and emission characteristics of diesel engine fueled with diesel/methanol/n-butanol blends. (15th April 2022) - Zhang, Zhiqing; Tian, Jie; Xie, Guangling; Li, Jiangtao; Xu, Wubin; Jiang, Feng; Huang, Yuanxing; Tan, Dongli
Highlights: Different diesel/methanol/n-butanol blend fuels are employed in this work. Effects of fuel additive rate on spray, combustion and emission characteristics are investigated. A computational modeling is developed by the chemical kinetics mechanism. Methanol additive and n-butanol play very important roles. Abstract: In this work, the diesel engine fueled with diesel/methanol/ n -butanol blended fuel was employed to investigate the effects of different fuel blending ratios on the spray, combustion, and emission characteristics of diesel engine in term of cylinder pressure, cylinder temperature, heat release rate, brake specific fuel consumption, brake power, brake thermal efficiency, NOx emission, soot emission, CO emission, and HC emission. The model was developed by a three-dimensional CFD model in CONVERGE and was verified by the experiment results. In addition, an improved chemical kinetic mechanism including 359 reactions and 77 species was employed to simulation the combustion processes. The results showed that diesel/methanol/n-butanol blends played an essential role in the fuel spray and combustion processes. The blended fuel had longer ignition delay, higher cylinder pressure, and higher peak heat release rate compared with diesel. Moreover, the occurrence of micro-explosion improves the blending of fuel and air. More specifically, the diesel/methanol/n-butanol blends could reduce NOx, CO, soot, and HC emissions. It can be found that the best blending ratio of blended fuel is 70%diesel + 20%methanol + 10%n-butanol. Therefore, the diesel/methanol/ n -butanol blended fuel can improve the combustion and emission characteristics of the engine.